Genetic basis of lacunar stroke: a pooled analysis of individual patient data and genome-wide association studies - Traylor, M; Persyn, E; Tomppo, L; Klasson, S; Abedi, V; Bakker, MK; Torres, N; Li, L; Bell, S; Rutten-Jacobs, L; Tozer, DJ; Griessenauer, CJ; et al. (Elsevier, 2021)
Background The genetic basis of lacunar stroke is poorly understood, with a single locus on 16q24 identified to date. We sought to identify novel associations and provide mechanistic insights into the disease.